Theocracy, Eschatology, and the Ephemeral Church: Graham Ward and the "Crisis of Democracy". Issue 4 (3rd July 2016) - Miller, Daniel
Abstract : This article offers a critical assessment of Graham Ward's political theology and critique of modern democracy. Ward argues that modern democracy expresses a nihilistic metaphysics and lacks an adequate account of the embodiment of sovereignty within the social, with the result that it tacitly harbors totalitarianism. As an alternative, Ward advances a theocratic model of the social, with the aim of providing an account of the social embodiment of sovereignty lacking in democracy. The article argues that Ward is ultimately unsuccessful in this attempt. His eschatological focus separates the church from the world, undermining his account of the embodiment of sovereignty and reinforcing the very emptiness at the heart of the social his theology is intended to counter.